THE EFFECTS OF STUDENT’S PERCEPTION ON TEACHER PERFORMANCE AND LEARNING MOTIVATION TOWARDS STUDENT’S ENGLISH ACHIEVEMENT - Nur Aeni; Supadi Supadi (INFERENCE: Journal of English Language Teaching, 2020)
Abstract: This research is a kind of survey and aims to find out and analyze empirically the effects of student’s perception on teacher performance and learning motivation towards student’s achievement in English subject. The object population of this research is private junior high students in Indramayu.  The sample was gained through simple random sampling. The collection of the data is done by questionnaire for both independent variables and by teachers’ file mid-term test for dependent variable. The gained data was analyzed by using correlation technique and multiple regressions. The result of this research is: 1) There are any significant effects of students perception on teacher performance and learning motivation jointly towards students’ achievement in English subject.  It is proved by Sig. = 0.000 < 0.05 and Fo = 49.077; 2) There is a significant effect of students’ perception on teacher performance towards students’ achievement in English subject.  It is proved by Sig. = 0.000 < 0.05 and to = 5.009; 3) There is a significant effect of learning motivation towards students’ achievement in English subject.  It is proved by and Sig. = 0.000 < 0.05 and to = 6.773.  It means that the students’ achievement in English subject is sufficient influenced by students’ perception on teacher performance and learning motivation.Key Words: Students’ Perception; Teacher Performance; Learning Motivation; Students Achievement.